2015
DOI: 10.1111/desc.12348
|View full text |Cite
|
Sign up to set email alerts
|

Emotional experience in music fosters 18‐month‐olds' emotion–action understanding: a training study

Abstract: We examine whether emotional experiences induced via music-making promote infants' use of emotional cues to predict others' action. Fifteen-month-olds were randomly assigned to participate in interactive emotion training either with or without musical engagement for three months. Both groups were then re-tested with two violation-of-expectation paradigms respectively assessing their sensitivity to some expressive features in music and understanding of the link between emotion and behaviour in simple action seq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 78 publications
(98 reference statements)
1
14
0
1
Order By: Relevance
“…Because music is integral to parent-infant interaction, we argue that infants can draw on the affective information coded in music to represent others’ intention. Siu and Cheung [ 26 ] trained 15-month-olds on the association between various emotions and their accompanying facial expressions and body movements over three months, either with or without engaging the infants with music during training. Their findings showed that musical engagement not only promoted the infants’ sensitivity to musical expressions but also facilitated their understanding of the link between emotion and behaviour in a non-musical context.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because music is integral to parent-infant interaction, we argue that infants can draw on the affective information coded in music to represent others’ intention. Siu and Cheung [ 26 ] trained 15-month-olds on the association between various emotions and their accompanying facial expressions and body movements over three months, either with or without engaging the infants with music during training. Their findings showed that musical engagement not only promoted the infants’ sensitivity to musical expressions but also facilitated their understanding of the link between emotion and behaviour in a non-musical context.…”
Section: Introductionmentioning
confidence: 99%
“…The third question is whether emotional representation in music and non-musical emotion-action understanding are naturally correlated, and if they are, at what age the relationship would become observable. We hypothesise the relationship because both abilities may be supported by the same underlying, more generalised capacity to represent others’ emotional states, which is fundamental to the infant’s early social development [ 26 ]. This generalised capacity is assumed to underpin non-musical facial-vocal expression, goal-directed action, as well as musical expression.…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with this, musicians show stronger responses to emotional speech prosody than non-musicians in regions implicated in modality-independent inferences about others’ mental states, including the medial prefrontal and anterior cingulate cortices 26 . Additionally, training studies indicate that musical activities enhance aspects of infants’ socio-emotional functioning beyond music/pitch processing, including the understanding of others’ actions based on vocal and visual affective cues 27 , and nonverbal communication and social interaction skills 28 .…”
mentioning
confidence: 99%
“…One study showed that when 4‐year‐olds make music in a group (compared with physically similar group activity without music), they then act more prosocially toward other members of that group (Kirschner & Tomasello, ). Similarly, when engaged in an emotion training program with or without music, 18‐month‐old infants who had engaged in the music program had better knowledge of emotional expression and the intention‐action link (i.e., theory of mind) than infants who had participated without music (Siu & Cheung, ).…”
Section: Research Programs In the Artsmentioning
confidence: 99%